Temática de Vallejo (Thematic of Vallejo) (1945) by Enrique Azálgara Ballón: rescue and appraisal - Yufra, Juan Wilfredo (2023)
The work, as well as the life of César Vallejo, has been critically approached throughout one hundred years. And in this chronological journey, Enrique Azálgara Ballón’s thesis Temática de Vallejo (1945) was relegated from the bibliographic collection and critical studies of Vallejo’s poetry. The present article is oriented to give news of that text and to expose its structure, the formal, critical, and aesthetic conditions that were promoted in an early period of Vallejo’s studies.